Inhibition of cGAS ameliorates acute lung injury triggered by zinc oxide nanoparticles. (15th January 2023) - Jiang, Ziqi; Jiang, Yu; Fan, Jingchuan; Zhang, Jun; Xu, Ge; Fan, Yinzhen; Zhang, Liyu; Qin, Xia; Jiang, Xuejun; Mao, Lejiao; Liu, Gang; Chen, Chengzhi; et al.
Abstract: Purpose: Zinc oxide nanoparticles (ZnONPs) have been widely used in various industrial and biomedical fields. Occupational or accidental inhalation exposure to ZnONPs might lead to acute lung injury (ALI). Cyclic GMP-AMP synthase (cGAS) and stimulator of interferon genes (STING) are critical for the initiation and expansion of inflammation and contribute to tissue injury; however, the role and mechanism of the cGAS-STING pathway in ALI-induced by ZnONPs are unclear. Methods: Male C57BL/6 J mice were intratracheally injected with ZnONPs (0.6 mg/kg) or mock. The mice were euthanized and the degree of lung injury was determined 3 days after the instillation of ZnONPs. The BEAS-2B cell line was used as a cell model to investigate the cytotoxicity of ZnONPs in vitro. Results: We found that ZnONPs inhalation induced ALI in mice, manifested by exacerbated lung pathological changes, mitochondrial damage, oxidative stress and inflammation. Interestingly, cGAS and STING were activated in the lung tissues of the mice and BEAS-2B lung epithelial cells treated with ZnONPs. More importantly, we illustrated that the cGAS inhibitor RU.521 inhibited the activation of the cGAS-STING pathway, further decreased oxidative stress and inflammation, and led to ameliorated lung injury in mice treated with ZnONPs. Conclusion: This study demonstrated that ZnONPs trigger the activation of the cGAS-STING pathway, which plays an important role in ZnONPs-induced ALI. Inhibition of cGAS with RU.521 mitigates the oxidative stress induced by ZnONPs, suggesting that targeting the cGAS-STING pathway may be a feasible strategy to ameliorate the pulmonary injury caused by nanoparticles. Graphical Abstract: ga1 Highlights: ZnONPs caused acute lung injury in mice and cell death in lung epithelial cells BEAS-2B. ZnONPs induced activation of cGAS-STING pathway in vivo and in vitro. Inhibition of cGAS with RU.521 ameliorated acute lung injury induced by ZnONPs in mice. Inhibition of cGAS with RU.521 inhibited cell death induced by ZnONPs in BEAS-2B cells.